Urea and soybean meal compared for cows on winter bluestem pasture - R.W. Swanson; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1970)
This test compared urea supplement (hand-fed), urea supplement (self-fed), and soybean meal (SBM) supplement (hand-fed) with cows on winter bluestem pasture. The supplements were formulated to supply the same amount of protein and total digestible nutrients. Salt was fed free choice with the hand-fed supplement.
Keywords: Cattlemen' s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Urea; Soybean meal; Bluestem pasture